Atypical presentations of hypothyroidism and associated problems in Ibadan, Nigeria (2015)
Background: Hypothyroidism can present atypically making its recognition difficult especially in resource limited settings. Case presentation and management: Two children presented with atypical features of hypothyroidism with resultant delay in diagnosis. Patient I presented with persistent respiratory distress, facial swelling and recurrent syncopal attacks. Cardiovascular examination was normal except for pulmonary hypertension. He did not respond to conventional supportive therapy and hypothyroidism was discovered much later. Patient II was a seven month old male infant with abdominal swelling, bilateral pitting leg edema, poor weight gain and delayed developmental milestones. Examination revealed ascites and pericardial effusion. He was being managed for protein energy malnutrition until he was found to have hypothyroidism and was successfully managed with L thyroxin. Conclusion A typical presentations of hypothyroidism in resource limited settings can result in delay in diagnosis and treatment which can lead to unnecessary morbidity and mortality. High index of suspicion and expertise are therefore required.